Propranolol Sensitizes Vascular Sarcoma Cells to Doxorubicin by Altering Lysosomal Drug Sequestration and Drug Efflux - Saha, Jhuma; Kim, Jong Hyuk; Amaya, Clarissa N.; Witcher, Caleb; Khammanivong, Ali; Korpela, Derek M.; Brown, David R.; Taylor, Josephine; Bryan, Brad A.; Dickerson, Erin B. (Frontiers in Oncology, 2021)
Angiosarcoma is a rare cancer of blood vessel–forming cells with a high patient mortality and few treatment options. Although chemotherapy often produces initial clinical responses, outcomes remain poor, largely due to the development of drug resistance. We previously identified a subset of doxorubicin resistant cells in human angiosarcoma and canine hemangiosarcoma cell lines that exhibit high lysosomal accumulation of doxorubicin. Hydrophobic, weak base chemotherapeutics, like doxorubicin, are known to sequester within lysosomes, promoting resistance by limiting drug accessibility to cellular targets. Drug synergy between the beta adrenergic receptor (B-AR) antagonist, propranolol, and multiple chemotherapeutics has been documented in vitro, and clinical data have corroborated the increased therapeutic potential of propranolol with chemotherapy in angiosarcoma patients. Because propranolol is also a weak base and accumulates in lysosomes, we sought to determine whether propranolol enhanced doxorubicin cytotoxicity via antagonism of B-ARs or by preventing the lysosomal accumulation of doxorubicin. B-AR-like immunoreactivities were confirmed in primary tumor tissues and cell lines; receptor function was verified by monitoring downstream signaling pathways of B-ARs in response to receptor agonists and antagonists. Mechanistically, propranolol increased cytoplasmic doxorubicin concentrations in sarcoma cells by decreasing the lysosomal accumulation and cellular efflux of this chemotherapeutic agent. Equivalent concentrations of the receptor-active S-(-) and -inactive R-(+) enantiomers of propranolol produced similar effects, supporting a B-AR-independent mechanism. Long-term exposure of hemangiosarcoma cells to propranolol expanded both lysosomal size and number, yet cells remained sensitive to doxorubicin in the presence of propranolol. In contrast, removal of propranolol increased cellular resistance to doxorubicin, underscoring lysosomal doxorubicin sequestration as a key mechanism of resistance. Our results support the repurposing of the R-(+) enantiomer of propranolol with weak base chemotherapeutics to increase cytotoxicity and reduce the development of drug-resistant cell populations without the cardiovascular and other side effects associated with antagonism of B-ARs.